Gear Up : Test Your Business Model Potential and Plan Your Path to Success - Ramfelt, Lena.; Kjellberg, Jonas; Kosnik, Thomas J. (Hoboken : Wiley, 2014)
Transform your business idea into high potential venturesBig, bright and brilliant, Gear Up is an engaging and practical workbook for anyone looking to pursue a fresh business opportunity or grow an existing one. It's a bootcamp, with clear, easy-to-follow steps to test your business idea, assess its potential and make it work! Based on a revolutionary 9-component framework, Gear Up offers entrepreneurs, intrapreneurs and innovative executives a toolkit to bring their ideas to life and transform them into high potential ventures. Gear Up of.
Hit where it hurts: the brutal truthidentify the risks; customers; delight; customer acquisition; business model; partners; competitors; go global; team; high stakes, no prisoners; be prepared to shoulder the blame; sync your gears; is there a pain for your delight?; sync your sales formula; is your unique sales formula made even more unique by your way of working with partners?; are you ready to go global?; spin the gears!; take action; make mistakes; celebrate success; there is no end; you don't have to trust us; tom kosnik; lena ramfelt; jonas kjellberg; ... the creative guys, ulf and johan.
Print version record.
And the wording.
John Wiley and Sons
Keywords: Marketing research; New business enterprises; Business planning; Entrepreneurship; Marketing -- Recherche; Nouvelles entreprises; Entrepreneuriat; entrepreneurs; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Business planning; Entrepreneurship; Marketing research; New business enterprises